Children, Fetuses, and the Non-Existent: Moral Obligations and the Beginning of Life. Issue 4 (22nd July 2021) - Jackson, Elizabeth
Abstract: The morality of abortion is a longstanding controversy. One may wonder whether it is even possible to make significant progress on an issue over which so much ink has already been spilled and there is such polarizing disagreement (Boyle, 1994, The Journal of Medicine and Philosophy 19:183–200). The papers in this issue show that this progress is possible—there is more to be said about abortion and other crucial beginning-of-life issues. They do so largely by applying contemporary philosophical tools to moral questions involving life's beginning. The first two papers defend the pro-life view from recent objections involving miscarriage and abortion doctors. The third shows how the social model of disability and the concept of transformative experience apply to classic debates like abortion and euthanasia. The final two papers address how rights and harms apply to children and to beings that do not yet exist. All five papers make a noteworthy contribution to the moral issues that arise at the beginning of life.